Cloning of a gene cluster encoding biphenyl and chlorobiphenyl degradation in Pseudomonas pseudoalcaligenes. - Furukawa, K (1986)
A gene cluster encoding biphenyl- and chlorobiphenyl-degrading enzymes was cloned from a soil pseudomonad into Pseudomonas aeruginosa PAO1161. Chromosomal DNA from polychlorinated biphenyl-degrading Pseudomonas pseudoalcaligenes KF707 was digested with restriction endonuclease XhoI and cloned into the unique XhoI site of broad-host-range plasmid pKF330. Of 8,000 transformants tested, only 1, containing the chimeric plasmid pMFB1, rendered the host cell able to convert biphenyls and chlorobiphenyls to ring meta cleavage compounds via dihydrodiols and dihydroxy compounds. The chimeric plasmid contained a 7.9-kilobase XhoI insert. Subcloning experiments revealed that the genes bphA (encoding biphenyl dioxygenase), bphB (encoding dihydrodiol dehydrogenase), and bphC (encoding 2,3-dihydroxybiphenyl dioxygenase) were coded for by the 7.9-kilobase fragment. The gene order was bphA-bphB-bphC. The hydrolase activity, which converted the intermediate meta cleavage compounds to the final product, chlorobenzoic acids, and was encoded by a putative bphD gene, was missing from the cloned 7.9-kilobase fragment.